The Bourne supremacy [videorecording (Blu-Ray)] - Gilroy, Tony; Damon, Matt; Potente, Franka, 1974-; Cox, Brian, 1946-; Stiles, Julia, 1981-; Urban, Karl, 1972-; Mann, Gabriel; Allen, Joan, 1956-; Csokas, Marton, 1966-; Roden, Karel, 1962-; Arana, Tomas, 1955-; Gallop, Tom; et al. (Universal, 2009)
Jason Bourne has abandoned his life as a CIA assassin and has been traveling beneath the agency's radar. He has been able to reconnect with Marie, the woman he loves. But Bourne is still haunted by vivid dreams and troubling memories of his days as a killer, and he's not certain how much really happened and how much is a product of his imagination. When Bourne is led out of hiding by circumstances beyond his control, he must reconcile his past and present as he struggles to keep Marie out of harm's way and foil an international incident with dangerous consequences.